ANALISIS DISAIN FILTER LC UNTUK SISTEM DAYA - Gustiono, Rusli (UMP, 2011)
Static converter and electronic device are able to generate harmonics current. Harmonics current can causes overheating of rotational machinery, transformator, magnetic contactor and cable of line distribution. Harmonic current effect is able to be reduced with using harmonic filter. Actually, for significant harmonic reduction must do field experiment or trial but determine resonance frequency, value of induktor and capacitor are first step in design filter before to do field experiment. This papper to intoduce other analysis in determining or calculating resonance frequency which be basic in harmonic filter design. Key word: frequency resonance, harmonic filter